2023
DOI: 10.1098/rsos.221487
|View full text |Cite
|
Sign up to set email alerts
|

Wide-gamut structural colours on oakblue butterflies by naturally tuned photonic nanoarchitectures

Abstract: The iridescent structural colours of butterflies, generated by photonic nanoarchitectures, often function as species-specific sexual signals; therefore, they are reproduced precisely from generation to generation. The wing scales of oakblue hairstreak butterflies (genus Arhopala , Theclinae, Lycaenidae, Lepidoptera) contain multi-layer photonic nanoarchitectures, which can generate a wide range of structural colours, from violet to green. By scanning (SEM) and cross-sectional transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…The integrating sphere collects all light reflected the upper hemisphere from the sample through a spot 5 mm in diameter, which contains hundreds of cover scales, thus integrating the unique, highly angle-dependent reflectance. The measured wing reflectances cover a smaller wavelength range compared to males of genus Arhopala where a similar structural tuning of photonic nanoarchitectures was found [33], although the shape and the width of the reflectance peaks are significantly different from each other. This results in characteristically different hues of structural colors, which were found to be consistent with the photographs (Figure 1), when the measured reflectance spectra were converted into the CIE 1931 chromaticity diagram (Figure 2b) [34].…”
Section: Resultssupporting
confidence: 51%
“…The integrating sphere collects all light reflected the upper hemisphere from the sample through a spot 5 mm in diameter, which contains hundreds of cover scales, thus integrating the unique, highly angle-dependent reflectance. The measured wing reflectances cover a smaller wavelength range compared to males of genus Arhopala where a similar structural tuning of photonic nanoarchitectures was found [33], although the shape and the width of the reflectance peaks are significantly different from each other. This results in characteristically different hues of structural colors, which were found to be consistent with the photographs (Figure 1), when the measured reflectance spectra were converted into the CIE 1931 chromaticity diagram (Figure 2b) [34].…”
Section: Resultssupporting
confidence: 51%
“…The use of butterfly wings for building hybrid photocatalytic platforms based on biological architectures with complex, hierarchic structures from the nanometre to centimetre scale opens a wide route to combine various photocatalytic nanoparticles with thin films conformally deposited by atomic layer deposition that allows spectral engineering of the optical properties of the photocatalyst in order to tune them to the specific absorption of the substances to be eliminated [ 55 , 56 ]. All over the world, numerous butterfly families possess intense colours of structural origin; for example, we recently investigated several species from the genus Arhopala that covers the spectral range from the UV to green [ 19 ]. In our work focusing on Morpho butterflies, we were able to increase the catalytic efficiency of the butterfly wings covered by a conformal 20 nm thin layer of ZnO by about ten times as compared to a flat glass substrate [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Working with butterflies with photonic nanoarchitectures in their wing scales with roles in sexual signalling [ 17 , 18 , 19 , 20 ] or camouflage [ 21 , 22 ], we faced the problem that the availability of museum samples is restricted, and in many interesting cases, destructive analyses are impossible. Moreover, the variables, which may influence the scale development and formation during the metamorphosis of the individual insect hitherto remain unexplored [ 18 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The attainment of blue structural coloration holds significance in both scientific and engineering realms, given the scarcity of blue pigments in living organisms owing to their intricate biochemistry [19]. For example, recent research by Piszter et al has demonstrated that oakblue hairstreak butterflies exhibit iridescent colors ranging from violet-to-green due to the presence of multi-layered photonic nanostructures with varying refractive indices in their scale morphology [20]. The modulation of structural elements within these photonic nanostructures results in a spectrum of structural colors.…”
Section: Introductionmentioning
confidence: 99%